The role of acculturation in migrants' use of gynecologic emergency departments. Issue 1 (28th January 2020) - Schwachenwalde, Sabina; Sauzet, Odile; Razum, Oliver; Sehouli, Jalid; David, Matthias
Abstract: Objective: To examine whether acculturation of migrant patients is a predictor of non‐urgent use of gynecologic emergency departments (GEDs). Methods: A cross‐sectional study based on standardized questionnaire interviews among migrant (n=477) and non‐migrant (n=246) women attending a GED in Berlin, Germany, between 2017 and 2018. Non‐urgent GED use was defined by health system (e.g., no hospital admission) or patient (e.g., low subjective urgency) criteria. Acculturation was assessed by the Frankfurt Acculturation Scale. Logistic regressions were calculated with non‐migrants as the reference. Results: Relative to migrants, low acculturation of migrants had no significant effect on overall non‐urgent GED use. However, low acculturation was a significant predictor of non‐urgent use if defined only by health system criteria (adjusted odds ratio [AOR], 1.58; 95% confidence interval [CI], 1.02–2.44; P =0.041). Inversely, low acculturation had a significant negative effect on non‐urgent use if defined only by patient criteria (AOR, 0.58; 95% CI, 0.38–0.90; P =0.014). Conclusion: Low‐acculturated migrants were more prone to non‐urgent GED use as defined by health system criteria, and might have a distorted perception of urgency. According to their perception, however, low‐acculturated patients showed appropriate GED use for urgent complaints, indicating that they are insufficiently cared for by the healthcare system. Abstract : Low acculturation predicted non‐urgent gynecologic emergency department use when use was defined by health system criteria, but not when it was defined by patient criteria.